Efeitos da exposição pré-natal ao etanol e ao chumbo, isoladamente e em associação, sobre a pressão arterial e a reatividade da aorta de ratos recém-desmamados - Vieira, José Sérgio Possomato [UNESP] (2014)
Introduction: although the literature reports cardiovascular changes induced by exposure to ethanol and lead (Pb) alone in adulthood, few studies focus on postnatal cardiovascular effects of exposure to ethanol and/or Pb in utero. Objectives: it was to investigate possible changes in the cardiovascular responses of weaned rats prenatally exposed to ethanol and Pb, alone and in combination. Still, advancing our understanding of the mechanisms involved in these changes. Materials and Methods: mothers were separated in 4 groups: control - received drinking water ad libitum ; Pb - received lead 500 ppm ad libitum during pregnancy ; EtOH - received a solution of 10% ethanol ad libitum in drinking water during pregnancy , and Pb / EtOH - both protocols in combination. Male Wistar rats (25 to 28-day old) from exposed mothers were used. The animals were sacrificed and thoracic aortic rings were collected and kept in organ bath containing Krebs- Henseleit solution, 37°C, pH 7.4, saturated with 95% O2 and 5% CO2. Concentration-effect curves to L-NAME, acetylcholine (ACh) in absence and presence of indomethacin and/or L-NAME, and sodium nitroprusside were obtained in intact and/or denuded aortas. It was also evaluated the blood pressure of 25-day old rats from all groups. Effective concentration 50% (EC50) and maximum response (MR) were evaluated (MANOVA/Tukey). Results: association of Pb exposure and ethanol in utero, but not the isolated protocols, determined hypertension on the 25th day of postnatal life (systolic - control 135.5 ± 3.0, Pb/EtOH 157.8 ± 4.6*; diastolic - control 97.5 ± 1.4, Pb/EtOH 125.9 ± 3.2*, *P < 0.05, n=11). None of the protocols determined any change in reactivity of intact and denuded aortas to L-NAME and sodium nitroprusside (MR and EC50) and EC50 to ACh in intact aortas (data not shown). Removal of endothelium abolished vasorelaxation to ACh. Unlike in utero exposure to Pb ...